Canine Pyometra: Current Perspectives on Causes and Management – A Review - Kumar, Alok; Saxena, Atul (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Canine pyometra is a pathological condition of endometrium which results in accumulation of purulent semisolid substance in uterus. Canine pyometra is a sequlae of cystic endometrial hyperplacia (CEH) which results from hormonal imbalance. Despite of enormous veterinary medical research and development, still its main aspect of etio-pathology is not fully known. Canine pyometra is mostly associated with other similar uterine pathological conditions, i.e., hydrometra, mucometra and chronic endomertitis. cervix as open-cervix or closed-cervix; however Canine pyometra is a common reproductive syndrome of intact, sexually mature bitches during met/diestrous stage with various clinical as well as pathological signs specific to reproductive system along with systemic signs (Fransson, 2003). Other terms to describe canine pyometra in relation to pathogenesis like chronic endometritis, chronic purulent metritis, cystic endometrial hyperplasia (CEH) or cystic endometrial hyperplasia - pyometra complex etc. also coined (Sandholm et al., 1975). Canine Pyometra can be categorized based on status of closed type is more serious condition, which needs surgical intervention so as to prevent concomitant sepsis and fatality (Smith, 2006). Pyometra can be defined as pathological condition of uterus in which there is accumulation of purulent semisolid-liquid substance inside the uterus of intact bitches, generally during post progesterone dominant phase of estrous cycle. Several authors suggested that pyometra should be classified as CEH- pyometra complex because of the fact that subacute endometritis later